BOOK REVIEWS (Journal of Finance, 1968)
Book reviewed in this article: Aggregate Theory and Policy: Federal Reserve Monetary Policy, 1917‐1933 . By E lmer R. W icker . Biddle's Bank: The Crucial Years . By J ean A lexander W ilburn . Business Finance and Investment: The Capital Expenditure Decision . By G. D avid Q uirin . Cases in Financial Decision Making . By R ichard L. N orgaard and D onald E. V aughn . Business Financial Management . By G ilbert W. C ooke and E dwin C. B omeli . Financial Institutions and Markets: Trends in Corporate Quality . By T homas R. A tkinson , with the assistance of E lizabeth T. S impson . The Consumer Finance Industry: Its Costs and Regulation . Edited by J ohn M. C hapman and R obert P. S hay . Money, Banking and the Economy . By J ohn A. C ochran . Issues in Banking and Monetary Analysis . Edited by G iulio P ontecorvo , R obert P. S hay , and A lbert G. H art . Money and Economic Activity: Readings in Money and Banking , 3rd ed. Edited by L awrence S. R itter . International Finance: Fiscal and Monetary Problems in Developing States: Proceedings of the Third Rehovoth Conference . Edited by D avid K rivine .